If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 1(11) = P Multiply 1 * 11 7 + 11 = P Combine like terms: 7 + 11 = 18 18 = P Solving 18 = P Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-1P' to each side of the equation. 18 + -1P = P + -1P Combine like terms: P + -1P = 0 18 + -1P = 0 Add '-18' to each side of the equation. 18 + -18 + -1P = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -1P = 0 + -18 -1P = 0 + -18 Combine like terms: 0 + -18 = -18 -1P = -18 Divide each side by '-1'. P = 18 Simplifying P = 18
| 7+1(X)=14 | | -11n-15n=8 | | -9(-5r-6+9m)= | | 7+1(2)=B | | -19=-0.5k | | 12-4x+9=0 | | (55-y)y=684 | | 6g+3g-10+3=47 | | -6x+5(-x+8)=139 | | 15(16)-14=c | | h+13.5=-13.5 | | 15(10)-14=c | | 15(2)-14=c | | 4x-9=4x+12 | | -8=3u-5 | | 10y-3y=7 | | (X+2)(x+10)=20 | | -2+9=1x+42 | | 7t+1+5t+8=162 | | -8v+3(v+8)=29 | | -45+15(x)=0 | | -45+15(0)=x | | 4x^3+10x^2-4x-10=0 | | y=-23000+4500x | | -7g=10-6g | | 3x-2y=4x | | -2v-6v=-16 | | 0=4e+4 | | 36-3x=312-x | | 7t+1=162 | | 2x-3+21=-3 | | -45+15(15)=x |